Wasting the rural: Meat, manure, and the politics of agro-industrialization in contemporary China. Issue 78 (January 2017) - Schneider, Mindi
Highlights: Proposes the industrial meat regime as an analytical concept. Explores shifting registers of value in China's pork sector. Uses Marx's metabolic rift to examine dialectics of concentration and separation. Examines how the rural is used a sink for offloading capitalist crises. Abstract: This paper uses pork as a lens on China's rural transformations. Taking the industrialization of pig farming in the reform era as a trace on broader processes of social and environmental change, it advances three arguments. First, the massive increase in pork production and consumption since 1978 has been propelled by an industrial meat regime . A party-state led and agribusiness-operated regime, it articulates modernist notions of meat-as-progress with the relentless drive for capital accumulation. Second, using Marx's concept of metabolic rift, the paper examines how processes of concentration in the industrial meat regime are at the same time processes of separation. This dialectical approach highlights the contradictions inherent in ongoing attempts to disembed capitalist production from biological and social relations. Finally, while official party-state discourse conceptualizes "the rural" as a production base for surplus value, and/or as a site for preserving environmental integrity, the paper's analysis reveals a further unofficial recasting of the rural: in the process of agroindustrialization, the rural is also a sink for offloading capitalist crises. Between the rivers of manure that flow from industrial livestock operations and contaminate rural waterways; the loss of soil nutrients and food calories in the inefficient conversion of grains and oilseeds into industrial meat; the erosion of agricultural knowledge and practice that accompanies the dispossession of China's farmers; and the shifting values of pigs, pork, and manure, this is a system that "wastes" the rural in service of capital.